2015
DOI: 10.1103/physrevlett.114.090502
|View full text |Cite
|
Sign up to set email alerts
|

Simulating Hamiltonian Dynamics with a Truncated Taylor Series

Abstract: We describe a simple, efficient method for simulating Hamiltonian dynamics on a quantum computer by approximating the truncated Taylor series of the evolution operator. Our method can simulate the time evolution of a wide variety of physical systems. As in another recent algorithm, the cost of our method depends only logarithmically on the inverse of the desired precision, which is optimal. However, we simplify the algorithm and its analysis by using a method for implementing linear combinations of unitary ope… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
853
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 624 publications
(863 citation statements)
references
References 24 publications
8
853
0
2
Order By: Relevance
“…With a future device of larger size and better coherence, we would be able to significantly improve the method of digitization. For instance, a digital simulation scheme based on the truncation of the Taylor series of the time-evolution operator [31] has been shown to exponentially outperform Trotterization in terms of , scale linearly with T (up to logarithmic factors), which implies a quadratic reduction in γ −1 , and scale much better with the number of terms for real world applications such as the simulation of chemistry [32,33]. As quantum hardware improves, the implementation of near-optimal schemes such as this becomes increasingly viable.…”
Section: Methods Of Digitization and Discussion Of Scalingmentioning
confidence: 99%
See 1 more Smart Citation
“…With a future device of larger size and better coherence, we would be able to significantly improve the method of digitization. For instance, a digital simulation scheme based on the truncation of the Taylor series of the time-evolution operator [31] has been shown to exponentially outperform Trotterization in terms of , scale linearly with T (up to logarithmic factors), which implies a quadratic reduction in γ −1 , and scale much better with the number of terms for real world applications such as the simulation of chemistry [32,33]. As quantum hardware improves, the implementation of near-optimal schemes such as this becomes increasingly viable.…”
Section: Methods Of Digitization and Discussion Of Scalingmentioning
confidence: 99%
“…However, in an error-corrected system the number of gates is in principle unconstrained, digitization can be made arbitrarily accurate, and one can move slower through critical parts of the evolution. While we have used Trotterization [30,31], with recent methods based on the truncation of Taylor series [32] the scaling of the digitization becomes appealing. See Supplementary Information for further motivations and discussions.…”
mentioning
confidence: 99%
“…That this can always be done is not totally trivial; see [37,38] for the state of the art. The spacetime history of the circuit V determines a connectivity or adjacency relation on the vertex or point set X ≡ {1, 2, .…”
Section: Jhep12(2016)055mentioning
confidence: 99%
“…In particular, it has been found that for systems with more than roughly 4 atoms, real space simulation is both more efficient and more accurate than second-quantized methods (Kassal et al, 2008;Kivlichan et al, 2016). These ideas have been combined with the recently developed sparse Hamiltonian simulation techniques (Berry et al, 2015a;Berry, et al, 2015b) to develop a real space simulation algorithm which outperforms its first-and second-quantized counterparts (Babbush, et al, 2015b;Babbush, et al, 2016) in certain regimes.…”
Section: Q U a N T U M A L G O R I T H M S A N D Protocols For Chemistrymentioning
confidence: 99%
“…The introduction of algorithms for the simulation of sparse Hamiltonians (Berry et al, 2015a;Berry et al, 2015b) made for a breakthrough in the field of quantum simulation.…”
Section: Q U a N T U M A L G O R I T H M S A N D Protocols For Chemistrymentioning
confidence: 99%